Respostas
respondido por:
0
x = - b +- raiz de b^2 - 4ac / 2a
x = - ( - 5 ) +- raiz de 25 - 24 / 2
x = 5 +- 1 / 2
x' = 6 / 2 = 3
x'' = 4 / 2 = 2
respondido por:
1
Olá Legocsc,
x² -5x + 6 = 0
Δ = b² - 4.a.c
Δ = -5² - 4 . 1 . 6
Δ = 25 - 4. 1 . 6
Δ = 1
x = (-b ± √Δ)/2a
x= -(-5) ± √1 /2.1
x= 5 ± 1/2
x'= 5 + 1 / 2
x'= 6/2
x'=3
x''= 5 - 1 /2
x''= 4/2
x''=2
S={3,2}.
Espero ter ajudado!
x² -5x + 6 = 0
Δ = b² - 4.a.c
Δ = -5² - 4 . 1 . 6
Δ = 25 - 4. 1 . 6
Δ = 1
x = (-b ± √Δ)/2a
x= -(-5) ± √1 /2.1
x= 5 ± 1/2
x'= 5 + 1 / 2
x'= 6/2
x'=3
x''= 5 - 1 /2
x''= 4/2
x''=2
S={3,2}.
Espero ter ajudado!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás